PENDAYAGUNAAN DUA JENIS ZINGIBERACEAE [C. mangga (temu mangga) dan K. angustifolia (kunci menir)] SEBAGAI SUMBER BAHAN IMUNOMODULATOR SECARA IN VITRO - Praptiwi .; Chairul . (Jurnal Teknologi Lingkungan, 2010)
Observation of imunomodulation properties of methanol extract derive (hexane,ethyl acetate, methanol/water) of Curcuma mangga (temu mangga) and Kaempferia angustifolia (kunci menir) had been carried out by in vitro assay. It was done by determining the phagocytised activity and capacity of macrophage cells of mice (Mus musculus) peritonium inducted with Staphyllococcus epidermidis. The result showed that each fraction had different phagocytised activity and capacity. Almost all of the fractions tested improved the activity (50–96 %) and capacity macrophage cells phagocytised compared to negative control (52 dan 502) and positive control (97 dan 1076). The positive control was 1000 ug Stimuno (Phyllanthus niruri extract), while the negative control was aquadest. The ethyl acetate fraction of Z. cassumunar (bangle) had highestphagocytised activity and capacity followed by C. mangga (temu mangga) and K. Angustifolia (kunci menir). It can be concluded that there were significant differences of phagocytised activity and capacity among fraction tested.Keywords : Zingiberaceae, Curcuma mangga, Kaempferia rotunda, Zingibercassumunar, immunomodulator, phagocytised, macrophage cells.